A study of the Human Platelet Antigen 1a (HPA-1a) antibody response in neonatal alloimmune thrombocytopenia (NAIT) - Allen, D; David L Allen (2013)
Neonatal alloimmune thrombocytopenia (NAIT) is caused by maternal alloantibodies against fetal platelet antigens inherited from the father and which are absent from maternal platelets. In Caucasians, antibodies against the Leu33 (HPA-1a) polymorphism of integrin β3 (part of the platelet αIIbβ3 complex) account for >70% of cases. Antenatal screening for these antibodies does not currently take place in the UK, partly because of the absence of sensitive, predictive tests. We hypothesized that the poor sensitivity and predictive abilities of current assays are due to the use of β3 in an inappropriate conformation, resulting in sub-optimal binding of HPA-1a antibodies. We hypothesized firstly that in vitro induced changes to αIIbβ3 might alter accessibility of the HPA-1a epitopes to alloantibodies, thus reducing assay sensitivity. Secondly, we hypothesized that HPA-1a antibodies are stimulated by, and preferentially recognise, β3 in association with αv, a molecule present on placental syncytiotrophoblasts, and that reactivity against platelet αIIbβ3 reflects only cross-reactivity with αvβ3. Our first hypothesis was proven by demonstrating that use of the cation chelating compound EDTA, used by many diagnostic laboratories as a component of assay reagents or present in blood samples as anticoagulant, resulted in significantly reduced assay sensitivity. These findings were confirmed in an international workshop. Support for our second hypothesis was provided by demonstrating enhanced reactivity of a small panel of examples of anti-HPA-1a against αvβ3 compared to αIIbβ3 and by molecular modelling data. We also showed that HPA-1a antibodies can inhibit platelet function by using a novel application of the ROTEM® delta thromboelastograph and an immunofluorescence assay in which we demonstrated blocking of platelet function using a monoclonal antibody, PAC-1, that binds only to activated αIIbβ3. These studies provide possible explanations for the poor sensitivity and predictive abilities of current assays and suggest further areas for research.